Determination of ecological efficiency in internal combustion engines: The use of biodiesel - Coronado, Christian Rodriguez [UNESP]; de Carvalho, Joao Andrade [UNESP]; Yoshioka, Juliana Tiyoko [UNESP]; Silveira, Jose Luz [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
This paper evaluates and quantifies the environmental impact from the use of some renewable fuels and fossils fuels in internal combustion engines. The following fuels are evaluated: gasoline blended with anhydrous ethyl alcohol (anhydrous ethanol), conventional diesel fuel, biodiesel in pure form and blended with diesel fuel, and natural gas. For the case of biodiesel, its complete life cycle and the closed carbon cycle (photosynthesis) were considered. The ecological efficiency concept depends on the environmental impact caused by CO(2), SO(2), NO(x) and particulate material (PM) emissions. The exhaust gases from internal combustion engines, in the case of the gasoline (blended with alcohol), biodiesel and biodiesel blended with conventional diesel, are the less polluting; on the other hand, the most polluting are those related to conventional diesel. They can cause serious problems to the environment because of their dangerous components for the human, animal and vegetable life. The resultant pollution of each one of the mentioned fuels are analyzed, considering separately CO(2), SO(2), NO(x) and particulate material (PM) emissions. As conclusion, it is possible to calculate an environmental factor that represents, qualitatively and quantitative, the emissions in internal combustion engines that are mostly used in urban transport. Biodiesel in pure form (B100) and blended with conventional diesel as fuel for engines pollute less than conventional diesel fuel. The ecological efficiency for pure biodiesel (B100) is 86.75%: for biodiesel blended with conventional diesel fuel (B20, 20% biodiesel and 80% diesel), it is 78.79%. Finally, the ecological efficiency for conventional diesel, when used in engines, is 77.34%; for gasoline, it is 82.52%, and for natural gas, it is 91.95%. All these figures considered a thermal efficiency of 30% for the internal combustion engine. Crown Copyright (C) 2008 Published by Elsevier Ltd. All rights reserved.
Keywords: Ecological efficiency; Engine; Biodiesel; Vehicular fuels; Combustion